2017
DOI: 10.1039/c7dt03279j
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of Co–N–C porous catalyst derived from metal organic complexes for highly effective ORR

Abstract: In this work, we reported a novel and slack rose-like metal organic precursor designed by coordinating p-phenylenediamine with cobalt ion. After subsequent pyrolysis and acid etching process, the as-prepared Co-N-C catalyst delivered a superior catalytic activity and long-term durability. Further applied in the Zn-air battery, it also displayed a comparable performance with 20% Pt/C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The combination of Co 4 N with high OER activity and Co−N−C with good ORR activity showed decent performance in rechargeable Zn‐air batteries. Following Meng's work, some other publication also reported the generation of transition metal nitrides (e. g., Fe 3 N, FeN x , CoN x ) or transition metal carbides (e. g., Fe 3 C, Co 3 C) from MOF precursors after high‐temperature calcination . However, due to the complexity of the composition, further investigation into the role of these transition metal compounds on oxygen catalysis and on rechargeable Zn–air batteries is still required.…”
Section: Mof‐derived Catalysts For Zn–air Batteriesmentioning
confidence: 97%
See 1 more Smart Citation
“…The combination of Co 4 N with high OER activity and Co−N−C with good ORR activity showed decent performance in rechargeable Zn‐air batteries. Following Meng's work, some other publication also reported the generation of transition metal nitrides (e. g., Fe 3 N, FeN x , CoN x ) or transition metal carbides (e. g., Fe 3 C, Co 3 C) from MOF precursors after high‐temperature calcination . However, due to the complexity of the composition, further investigation into the role of these transition metal compounds on oxygen catalysis and on rechargeable Zn–air batteries is still required.…”
Section: Mof‐derived Catalysts For Zn–air Batteriesmentioning
confidence: 97%
“…In this regard, hollow and core/shell structures,,,, 1D thin rods/bars,,,,,,,,,, 2D thin sheets,,,,,,, are shown to be favorable. In addition, highly interconnected 3D structures,,,, are also beneficial to improving the long‐range electronic conductivity of the cathode.…”
Section: Mof‐derived Catalysts For Zn–air Batteriesmentioning
confidence: 98%
“…The electrocatalytic performance of the decorated graphene should arise from the high specific surface area. However, many studies reported that the metal aggregation during high‐temperature pyrolysis processes probably decreases electrocatalytic activity . Therefore, graphene with highly‐dispersed CoN x species could be an ideal electrocatalyst if metal nanoparticles are prevented from aggregating during carbonization …”
Section: Methodsmentioning
confidence: 99%
“…The performance enhancement of the abovementioned electrocatalysts is usually attributed to the inclusion of Fe or Co nanoparticles as well as N species such as pyridinic N, pyrrolic N, graphitic N and Fe/Co-N x complex. [20][21][22][23][24][25][26][27][28][29][30] Nonetheless, the cost of SCM in these electrocatalysts is still relatively high and limits the practical application.…”
Section: Introductionmentioning
confidence: 99%